PERIODICITY OF DECISIONS OF SOME SYSTEM A FEW NONLINEAR DIFFERENTIAL EQUALIZATIONS OF AN EVEN ORDER - Краснодембський, Адам Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The terms of convergence of sequences which determine the upshots with the periodic components of some system of a few nonlinear differential equalizations of even order are set in the article.